Multi-criteria assessments of increasing supply air temperature in tropical data center - Zhou, Jing (2023)
With rapid development of information technology, the number and scale of data centers (DCs) increase rapidly. Therefore, cooling energy saving becomes crucial. This study proposes multi-criteria assessments of increasing supply air temperature (SAT) in the air-cooled DCs to analyze the interactions of internal and external factors in cooling systems comprehensively. Impacts of refrigerant charge (RC), evaporation pressure (EP) control limits, and hot aisle containment (HAC) with improvements in SAT are compared and analyzed according to the thermodynamic, economic, and thermoeconomic aspects. Overall, as SAT increases from 20 °C to 32 °C, the power usage effectiveness decreases by 16.8%–19.3%. Increase in RC leads to energy consumption and cost increasing at high SAT ranges, whereas high RC shows obvious advantages at the low SAT from the thermoeconomic aspects. Additionally, releasing EP control limits has significant advantages in reducing energy usage, and cumulative present worth of data center testbed can decrease by 5.2% and 6.0% at low and high RC operations, respectively. Return on investment and payback period analysis are also performed in the testbed with the HAC reform, and the payback period is about 1–3 years with the SAT setting range at 20–32 °C.